PRAKTEK PENCATATAN BUKU KAS DAN LITERASI KEUANGAN PADA KELOMPOK IBU RUMAH TANGGA DESA PADDINGING KECAMATAN SANROBONE KABUPATEN TAKALAR - Modding, Basri; Suriyanti, Suriyanti; Estika, Lala; Fitriani, Fitriani; Wahyuni, Nur (Arunika: Jurnal Pengabdian Masyarakat, 2022)
Abstract: The role of housewives is very important, including in financial planning. Because of the important role of housewives in managing finances, adequate education about financial literacy is needed. From the pre-survey data conducted by the Service Team, it was found that the financial literacy of housewives in the Desa Paddingnging Kecamatan Sandrobone Kabupaten Takalar that is low. The purpose of this activity is to increase literacy in managing finances. The method used is training and practice. Keywords: Financial Literacy; Housewife